БАЗОВІ ІНСТИТУЦІЇ ТА ЕКОНОМІЧНИЙ РОЗВИТОК ПОСТКОМУНІСТИЧНИХ КРАЇН ЦЕНТРАЛЬНОЇ І СХІДНОЇ ЄВРОПИ - Ватаманюк, О.; Островерх, П.; Саловський, О. (Financial and credit activity problems of theory and practice, 2021)
Abstract. Contrasting outcomes of economic reforms conducted by the post-communist countries in Central and Eastern Europe over the last thirty years seem to be directly associated with the peculiarities of their formal and informal institutions. The rapid pace and flexible adjustment of institutional changes, along with mindful heed towards existing institutional frameworks, have become the key to the success of more than a dozen of countries, which eventually and ultimately joined the European Union. In order to analyze the impact of institutions’ quality on economic development in post-socialist countries, the authors substantiate the approach, which outlines five basic groups of institutions: property, power, competition, innovations, and values. A number of indicators collected or calculated by international organizations such as the World Bank, Transparency International, The Heritage Foundation, among others, have been used to describe and quantify the impact of these institutions. In addition, they have been applied to construct and calculate composite indices for each of the five basic groups of institutions, as well as to generalize an integrated institutional index. The authors have chosen the World Bank data on gross domestic products per capita to illustrate the level of economic development of the studied countries. Subsequently, a list of simple linear and multiple regression models has been created, which facilitated identifying a statistically significant impact of an ample number of selected institutions on the level of well-being in post-socialist countries. In particular, the influence of power, innovation, and competition institutions is especially noticeable, also confirmed for the composite indices for these groups of institutions. Furthermore, in multiple regression models, a combination of one of the indicators of power or the corresponding composite index with the R&D expenditures’ share indicator and the Human development index seems a common pattern. In overall, different versions of the models built contain parameters that attribute to four of the five basic institutions. The absence of property-related indicators in these models could probably be explained via the nature of chosen indices and possibilities of the significant indirect impact of property institutions through the indicators of power institutions. Keywords: institutions, economic development, Central and Eastern European countries, institutional changes, basic institutions, regression analysis. JEL Classification B52, O17, O43, P30 Formulas: 0; fig.: 0; tabl.: 4; bibl.: 24.